Pengaruh Lingkungan Pendidikan dan Pemahaman Beragama terhadap Moderasi Beragama Siswa SMP Negeri 1 Kota Padang Panjang - Ernita Ernita; Fadriati Fadriati; David; Marjoni Imamora; Suharmon Suharmon (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2025)
This study was motivated by the importance of fostering moderate religious character among students in Indonesia's multicultural society. Religious moderation plays a crucial role in promoting tolerance, respect for diversity, and social harmony among people of different religious backgrounds from an early age. This study aimed to analyze the influence of the educational environment and religious understanding on students' religious moderation values at SMP Negeri 1 Kota Padang Panjang. The study employed a quantitative approach with a correlational design, supported by qualitative data obtained through interviews and observations. The sample was selected using a stratified random sampling technique based on Grade VIII and Grade IX students. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 25. The findings revealed that both the educational environment and religious understanding had a positive and significant influence, both partially and simultaneously, on students' religious moderation values. The coefficient of determination (R²) was 0.762, indicating that 76.2% of the variance in students' religious moderation values could be explained by the two independent variables, while the remaining 23.8% was influenced by other factors outside the research model. These findings suggest that creating a supportive educational environment and strengthening contextual religious understanding are essential in fostering students' religious moderation. Therefore, religious moderation values should be integrated into the curriculum, school culture, and learning practices as an integral part of character education.